Post-COVID-19 Cognitive Dysfunction: Methodological Foundations for Prevention and Correction Model - Anton V. Solodukhin; Andrey V. Seryy; Lidiia A. Varich (СибСкрипт, 2024)
The article introduces a comprehensive review of theoretical and experimental studies in the field of psychophysiological predictors of cognitive impairments in post-COVID-19 patients. The data obtained made it possible to design a model of psychological correction and prevention of post-COVID-19 cognitive dysfunction. This condition affects cognitive, behavioral, and psycho-emotional areas of mental activity. Functional changes involve poor mobility of nervous processes and short attention span, as well as changes in coping behavior and personality characteristics. Unlike older patients, teenagers experience fewer consequences for cardiovascular system and cognitive functions. As for gender differences, men restored their cognitive functions better when they came to grasp with their past experience. For women, recovery was associated with life meaning, planning, and goal setting. The resulting model for the prevention and psychological correction of post-COVID-19 cognitive dysfunction integrated the principles of systemic, information, cognitive, and personality-oriented approaches. It consisted of several structural elements that made it possible to support COVID-19 patients through all treatment stages, i.e., psychodiagnostics, psychocorrection, psychotherapy, and social and lifestyle adaptation.